2021
DOI: 10.1021/acs.jctc.0c00981
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Collective Variables of Molecular Transitions via Genetic Algorithms and Neural Networks

Abstract: With the continual improvement of computing hardware and algorithms, simulations have become a powerful tool for understanding all sorts of (bio)molecular processes. To handle the large simulation data sets and to accelerate slow, activated transitions, a condensed set of descriptors, or collective variables (CVs), is needed to discern the relevant dynamics that describes the molecular process of interest. However, proposing an adequate set of CVs that can capture the intrinsic reaction coordinate of the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 63 publications
4
39
0
Order By: Relevance
“…S2). Our profiles are validated by: 1) the previous result for the CAA sequence reported in [36]; 2) the consistent WCFto-HG free-energy difference between our inside and outside calculations; and 3) the relatively favored HG base pairing for the TAA sequence, which agrees with experimental evidence about the effect of A•T steps [21]. We run ∼ 7 ns with twelve walkers to calculate each free-energy profile; placing our total runtime to obtain the inside and outside profiles of one sequence at ∼ 168 ns.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…S2). Our profiles are validated by: 1) the previous result for the CAA sequence reported in [36]; 2) the consistent WCFto-HG free-energy difference between our inside and outside calculations; and 3) the relatively favored HG base pairing for the TAA sequence, which agrees with experimental evidence about the effect of A•T steps [21]. We run ∼ 7 ns with twelve walkers to calculate each free-energy profile; placing our total runtime to obtain the inside and outside profiles of one sequence at ∼ 168 ns.…”
Section: Discussionsupporting
confidence: 79%
“…The attractors successfully keep the paths separated, with the inside ones near θ = 0 and the outside ones flipping toward the major groove. The free-energy profile for the CAA sequence compares well to our results from [23] and [36], which consider only the 3' direction of rotation. To simplify the analysis of the numerous free-energy profiles, in Fig.…”
Section: Free-energy Differences and Barrierssupporting
confidence: 76%
See 1 more Smart Citation
“…26 This highly stable extra-helical conformation is inconsistent with the conventional idea about the stability of DNA, and provokes further discussion on the accuracy of force fields in describing the base pairing intermediates and transition pathways. Path sampling studies by Vreede et al 29 and Hooft et al 30 also revealed that partial opening of the A-T base pair is necessary for the conformational switching, but no stable open base paired intermediate conformation was observed.…”
Section: Introductionmentioning
confidence: 98%
“…Machine learning models have been widely utilized to determine the dominant CVs from trajectories obtained using MD simulations. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Furthermore, a feasible application is the nonlinear regression based on a deep neural network (DNN), which is expected to have a performance beyond that of the LR in searching for an appropriate RC. 67,72,73 In particular, nonlinear functions of a DNN with hidden layers will provide richer expressions when the number of CVs is drastically increased in the system of interest.…”
Section: Introductionmentioning
confidence: 99%